Histology To Prove Occurrence Somatic Embryogenesis In Drosera burmannii - Hafsa, Tayyab (2017)
The are certain traits of carnivorous plants that have intrigued people for years. Carnivorous plants are marvellous in the way they portray selection. Carnivorous plants are admired for their ornamental value, however, their true value lies in their medicinal properties. Unfortunately, due to these traits, carnivorous plants have become endangered. Plant tissue culture techniques are being utilised to conserve these endangered species. In vitro propagation allows production of disease free clones of plants on a large scale. In vitro plant regeneration is carried out via organogenesis and somatic embroygenesis (DSE) is preferred as single cells are involved which reduces somaclonal variation and chimera formation. The aim of this research was to use histological study to observe and confirm pre- and post-globulardevelopmant stages of SE in D. burmannii. Leaf explants of D. burmannii were previously induced on medium containing 0.01 mg/L thidiazuron (TDZ) to undergo SE. Leaf explants were fixed, embedded in paraffin wax, sectioned and stained to produce microscopic slides used in histological study. Stereo microscope analysis and histological study were carried out to observe morphological changes in those leaf explants. The pre- and post-globular morphological structures such as globular, heart, torpedo and germinating were identified via stereo microscope and histology approach. Observation of outer and inner morphology of globular, heart, torpedo and germinating embryos confirmed thatD. burmannii could be regenerated in vitro via SE. Even though was found that D.burmannii does not have a cotyledon stage, from torpedo stage it goes directly into germinating stage. However, the presence of a germinating stage proved that regeneration via SE had occured. It was concluded that D. burmannii regenerates via DSE and undergoes a unicellular pathway. Further research can be carried out tostudy nutritional factors to increase SE rate in D. burmannii.